Digital Marketing Strategy Navigation Assistance in an Effort to Strengthen Cigadung Village as a Sustainable Creative Tourism Destination - Andari, Rini; Yuniawati, Yeni; Gitasiswhara, Gitasiswhara (Master of Management Diponegoro University, 2024)
The evolution of tourism as a result of the COVID-19 epidemic is inextricably linked to technological advancements in the digital era. Tourist interest in alternative tourism is a potential for tourist villages to expand at present time, but with limited human resources, tourist villages have obstacles in being recognized by the larger community. This difficulty may be solved by leveraging digital marketing, with the awareness that academics play a vital role in collaborating with tourism villages in order to achieve the welfare of local citizens. This study was conducted using training and mentoring methods for the manager of the creative tourism village of Cigadung where the process was carried out for one year starting with preparation, training, implementation, and mentoring. The findings revealed that training without practice and mentoring has no effect on local residents' ability to develop their tourism village; thus, the mentoring carried out has a significant impact on assisting local residents' difficulties in advancing the creative tourism village of Cigadung, which has a lot of tourism potential. In this assistance, managers are provided an awareness and aid regarding push and pull marketing using social media, blogs, and websites. The implementation of this assistance is expected to be a reference for academics in providing community service, where implementation and practice are the main things and are significant enough to have an impact in advancing the welfare of tourist villages compared to just doing the theater without getting real responses from local residents of tourist villages.